The Guardians [compact disc, unabridged] - Grisham, John (Random House Audio, 2019)
In the small north Florida town of Seabrook, a young lawyer named Keith Russo was shot dead at his desk as he worked late one night. The killer left no clues behind. There were no witnesses, no real suspects, no one with a motive. The police soon settled on Quincy Miller, a young black man who was once a client of Russos. Quincy was framed, convicted, and sent to prison for life. For twenty-two years he languished in prison with no lawyer, no advocate on the outside. Then he wrote a letter to Guardian Ministries, a small innocence group founded by a lawyer/minister named Cullen Post. Guardian handles only a few innocence cases at a time, and Post is its only investigator. He travels the South fighting wrongful convictions and taking cases no one else will touch. With Quincy Miller, though, he gets far more than he bargained for. Powerful, ruthless people murdered Keith Russo, and they do not want Quincy exonerated.